Giant Cell Arteritis Presenting as Choroidal Infarction - Nikolaos Kopsachilis; Maria Pefkianaki; Anca Marinescu; Sobha Sivaprasad (Case Reports in Ophthalmological Medicine)
Background. Giant cell arteritis (GCA) is a systemic granulomatous vasculitis that affects large- and medium-sized arteries of the head and neck. Ocular manifestations of GCA usually are anterior ischaemic optic neuropathy (AION) or retinal vessel occlusion. Case Report. We report an interesting case of a 70-year-old man who presented with sudden vision loss and choroidal infarction in his left eye. Thorough clinical and paraclinical evaluation revealed an underlying GCA, the treatment of which prevented further vision loss and systemic complications. Conclusion. This is an unusual presentation of choroidal infarction associated with CGA and emphasizes the need of thorough systemic evaluation in patients with choroidal infarction.